Analysis of disease resistance of ZmERS4 -overexpressing rice - Wanyuan Huang; Jun Ning; Bo Su; Wenjie Liu; Ting Ding (PLoS ONE, 2025)
The discovery of the novel genes with disease resistance and the cultivation of new varieties of maize was considered as the most economical and efficient strategy for the disease stress. In previous studies, our research team had screened and obtained an ethylene receptor protein gene Zea mays Ethylene Response Sensor4 (ZmERS4) from the maize leaf, then ZmERS4 was overexpressed in rice, followed by the obtaining of the T3 homozygous transgenic rice. Besides, the disease resistance of the ZmERS4 -overexpressing rice was analyzed during the research, which revealed that the overexpression of ZmERS4 in rice could enhance the resistance to Xanthomonas oryzae pv. oryzicola(Xoc) by reducing the expression of the sugar transporter genes and activating the expression of salicylic acid (SA) signaling-related genes at 24h post-inoculation with Xanthomonas oryzae pv. oryzicola. Besides, an increasing trend could be observed in the hydrogen peroxide content, which could be attributed to the overexpression of ZmERS4. Furthermore, it was indicated by high-performance liquid chromatography-tandem mass (HPLC-MS/MS) spectrometry that the SA contents of ZmERS4-overexpressing rice exhibited a significant increasing trend after the pathogen infection. Nevertheless, the improved resistance of ZmERS4-overexpressing rice was relatively inhibited after the pretreatment of the SA biosynthetic inhibitor, 1-amino-benzotriazole (ABT). According to the above results, it was assumed that ZmERS4 exhibited significant functions during the regulation of rice resistance to Xanthomonas oryzae pv. oryzicola, and the regulatory functions were mainly based on the inducement of plant oxidative burst activity and activation of the SA signaling pathway. Overall, these findings could provide genetic resources and a data basis for the exploration and evaluation of valuable disease-resistant genes from maize.